Environmental Chemistry of Groundwater Near an Industrial Area, Northwest China - Wu, Jianhua; Li, Peiyue; Qian, Hui (Asian Journal of Chemistry, 2013)
An entropy-weighted water quality index was applied to assess the groundwater quality near an industrial park (China) where several metal smelting plants are located. The study shows that most physiochemical parameters except HCO3–, NO3-N, TDS, total hardness, F– and Mn are within the permissible limits of WHO standard or national standard of China. The excessive HCO3–, TDS, total hardness and F– are caused mainly by natural rock weathering processes, while that of NO3-N is caused by agricultural activities and the high content of Mn in groundwater is induced by both natural and human processes. The water quality indexes range from 27.94 to 128.94 %. Sixty five per cent of the total samples are of medium quality, 25 % are of good quality and the remaining 10 % are of poor quality. The high water quality indexes are caused by the excess NO3-N, total hardness and Mn which are mostly human induced.